2013
DOI: 10.4103/0973-7847.120515
|View full text |Cite
|
Sign up to set email alerts
|

Camellia sinensis (Tea): Implications and role in preventing dental decay

Abstract: Tea is one of the most commonly consumed beverages with bioactive compounds like polyphenols-flavonoids-catechins, which are thought to be responsible for the health benefits that have traditionally been attributed to the tea. These compounds have multi-dimensional effects such as antibacterial action, inhibitory action on the bacterial and salivary amylase and inhibition of acid production. This article outlines the possible role of these compounds coupled with the presence of high fluoride content in tea to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…2 The recent investigation associated with the bioactive compound like polyphenols-flavonoids-catechins of tea due to their antioxidant activities which contribute to human health benefits. 3,4 Pharmacological research indicates that tea leaf extract has pharmacological activities such as antidiabetic, anticarcinogenic, antiviral, antibacterial, antiinflammatory, anti-aging and immune boosting antioxidant activities which contribute to human health. 1,[5][6][7] This activity associated with the efficacy of tea for the prevention and treatment of diasease.…”
Section: Introductionmentioning
confidence: 99%
“…2 The recent investigation associated with the bioactive compound like polyphenols-flavonoids-catechins of tea due to their antioxidant activities which contribute to human health benefits. 3,4 Pharmacological research indicates that tea leaf extract has pharmacological activities such as antidiabetic, anticarcinogenic, antiviral, antibacterial, antiinflammatory, anti-aging and immune boosting antioxidant activities which contribute to human health. 1,[5][6][7] This activity associated with the efficacy of tea for the prevention and treatment of diasease.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies with different methodologies have evaluated anticariogenic effects of green tea, and almost all of them reported the capacity of green tea to inhibit dental caries. Goenka et al 56 gums and evaluated the effects of chewing green tea gums on building tooth resistance to acid attacks. They concluded that chewing green tea gums increases the resistance of dentin to acid.…”
Section: Discussionmentioning
confidence: 99%
“…GC, EGC and EGCG possess strong bactericidal as well as antibacterial activity. Certain studies have also shown an inhibitory effect of tea over the acid production by cariogenic bacteria thus imparting a caries protective action (Goenka, Sarawgi, Karun, Nigam, Dutta & Marwah, 2013).…”
Section: Introductionmentioning
confidence: 99%